Wilms tumor primary cultures capture phenotypic heterogeneity and facilitate preclinical screening - Lisa Götz; Jenny Wegert; Alireza Paikari; Silke Appenzeller; Sabrina Bausenwein; Christian Vokuhl; Taryn D. Treger; Jarno Drost; Christin Linderkamp; Dominik T. Schneider; Karen Ernestus; Steven W. Warman; et al. (Translational Oncology)
Wilms tumors (WT) are characterized by variable contributions of blastemal, epithelial and stromal elements, reflecting their diverse cellular origins and genetic drivers. In vitro models remain rare, despite a growing need to better characterize tumor biology and evaluate new treatments. Using three approaches, we have now established a large collection of long-term cultures that represent this diversity. Adherent WT cultures are predominated by stromal cells, 3D spheroids model blastema, and patient-derived organoid cultures of both tumor and healthy kidney tissue result in the preferential growth of epithelial cells. Adherent, spheroid and organoid cultures are also clearly distinguishable by their transcriptome. Preclinical drug screening experiments revealed sensitivity to a range of inhibitors, that are highly effective in other childhood solid tumors. Sensitivity was related to MYCN status, a marker associated with adverse outcome across human cancers including WT. The combination of the three culture techniques represents a promising tool to both explore tumor heterogeneity in vitro and to facilitate characterization of candidate driver genes, in order to improve treatment regimens in the future.